2005
DOI: 10.1016/j.ijsu.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline is efficacious in the treatment of complicated intra-abdominal infections

Abstract: TGC is efficacious in the treatment of patients with cIAIs and TGC met per the protocol-specified statistical criteria for noninferiority to the comparator, IMI/CIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 25 publications
3
49
0
2
Order By: Relevance
“…However, in reviewing the studies of tigecycline for FDA-approved indications, the agent demonstrated similar results when evaluated against its bactericidal comparators [6][7][8]. Further assessment of tigecycline in VAP studies postulated that the mortality risk may actually be attributed to suboptimal dosing of the agent [9].…”
Section: Tigecycline Concernsmentioning
confidence: 97%
“…However, in reviewing the studies of tigecycline for FDA-approved indications, the agent demonstrated similar results when evaluated against its bactericidal comparators [6][7][8]. Further assessment of tigecycline in VAP studies postulated that the mortality risk may actually be attributed to suboptimal dosing of the agent [9].…”
Section: Tigecycline Concernsmentioning
confidence: 97%
“…224 In one study of cIAI, the cure rate in the subgroup of patients with documented E. coli infection treated with tigecycline was 10% lower than that observed in the imipenem arm (88% vs 98%), in line with the lower clinical cure rate observed in the subgroup with complicated appendicitis (87% vs 100%). 229 This difference was not found in other studies in patients with cIAI. Regarding the severity of the infections, most were moderate, and immunocompromised patients were excluded.…”
Section: When and How Should Fosfomycin Be Used In The Treatment Of Imentioning
confidence: 63%
“…Regarding the severity of the infections, most were moderate, and immunocompromised patients were excluded. [221][222][223][224][225][226][227][228][229][230][231] Therefore, from the evidence provided by these studies it cannot be inferred that the efficacy of tigecycline in monotherapy would be the same in more severe infections.…”
Section: When and How Should Fosfomycin Be Used In The Treatment Of Imentioning
confidence: 95%
See 2 more Smart Citations